Clinical characteristics and long-term progression of young patients with acute coronary syndrome in Brazil - Soeiro,Alexandre de Matos (2015)
Objective In Brazil, there are few descriptions in the literature on the angiographic pattern and clinical characteristics of young patients with acute coronary syndrome, despite the evident number of cases in the population. The objective of this study was to evaluate which clinical characteristics are most closely related to the acute coronary syndrome in young patients, and what long-term outcomes are in this population.Methods This is a prospective observational study with 268 patients aged under 55 years with acute coronary syndrome, carried out between May 2010 and May 2013. Data were obtained on demographics, laboratory test and angiography results, and the coronary treatment adopted. Statistical analysis was presented as percentages and absolute values.Results Approximately 57% were men and the median age was 50 years (30 to 55). The main risk factors were arterial hypertension (68%), smoking (67%), and dyslipidemia (43%). Typical pain was present in 90% of patients. In young individuals, 25.7% showed ST segment elevation. Approximately 56.5% of patients presented with a single-vessel angiographic pattern. About 7.1% were submitted to coronary bypass surgery, and 42.1% to percutaneous coronary angioplasty. Intrahospital mortality was 1.5%, and the combined event rate (cerebrovascular accident/stroke, cardiogenic shock, reinfarction, and arrhythmias) was 13.8%. After a mean follow-up of 10 months, mortality was 9.8%, while 25.4% of the patients had new ischemic events, and 37.3% required readmission to hospital.Conclusion In the short-term, young patients presented with mortality rates below what was expected when compared to the rates noted in other studies. However, there was a significant increase in the number of events in the 10-month follow-up.